Key Factors Contributing to Assisting and Protecting Consumers of Organic Agricultural Products Using Modern Technologies - Thameur, Mohamed Bachir; Merrakchi, Abdelhamid (Journal of Excellence for Economics and Management Research, 2025)
This research paper aims to highlight the potential of utilizing modern technology in the growth of the safe agricultural sector, both in terms of the nutritional value of products and preserving consumer health, as well as supporting the national economy. It proposes the use of artificial intelligence (AI) and its applications to introduce consumers to organic ’Bio’ agricultural products, attract them, raise their awareness, and, on the other hand, help them avoid falling into the misconceptions propagated by many producers of such products and protect them. For this purpose, a survey was conducted targeting 124 consumers to identify as many scattered factors as possible for protecting consumers of these products, resulting in 14 factors. A second survey was then conducted, involving 657 individuals from around the world. Using exploratory and confirmatory factor analysis, we identified five key factors that effectively contribute to assisting and protecting this category of consumers, listed as follows: Tracking and Analysis, Detection of Counterfeit Products, Product Availability Location, Improvement of Product Quality, and Product Sizes, Shapes, and Conditions